STRATEGI DIFERENSIASI DALAM MENENTUKAN POSITIONING PASAR (Studi Kasus Minuman LEGA di Labuhanbatu) - Prayoga, Yudi; Dani, Ayu Rama (LPPM Universitas Labuhanbatu, 2020)
This study is intended to determine the differentiation strategy in determining market positioning (case study of LEGA drinks in Labuhanbatu). This research was conducted using a purposive sampling technique with the poulation that the consumer of LEGA drinks at Jln KH Dewantara, Kec. Rantau Selatan. a sample of 30 respondents who had consumed LEGA drinks in Labuhanbatu and the sampling method was carried out by giving questions in the form of questionnaires and interviews where each question answered would be expressed in numerical form based on the linkert scale. The analysis tool used is a simple analysis. Based on the results of data analysis and hypothesis testing, it is concluded that the independent variables partially affect the dependent variable, including product, service, personnel, and image have an effect on the market positioning of LEGA drinks in Labuhanbatu, with F count, namely, 61.678.